Cold-rolling and recrystallization textures of a nano-lamellar AlCoCrFeNi2.1 eutectic high entropy alloy. (May 2017) - Wani, I.S.; Bhattacharjee, T.; Sheikh, S.; Clark, I.T.; Park, M.H.; Okawa, T.; Guo, S.; Bhattacharjee, P.P.; Tsuji, N.
Abstract: The development of texture during cold-rolling and recrystallization was investigated in a AlCoCrFeNi2.1 eutectic high entropy alloy (EHEA). For this purpose, the as-cast alloy was cold-rolled to 90% reduction in thickness and annealed at temperatures ranging from 800 °C to 1200 °C. The microstructure of the as-cast EHEA showed a nano-lamellar mixture of L12 and B2 phases. The B2 phase was significantly harder than the L12 phase. Development of an ultrafine microstructure was observed after 90% cold-rolling. During cold-rolling, progressive disordering of the L12 phase was observed while the B2 phase maintained the ordered structure. The progressive disordering and development of a predominantly brass type texture in the L12 phase correlated well with profuse shear band formation during cold-rolling. The B2 phase showed the presence of the 111<110> component which was typical for cold-rolled B2 alloys. An ultrafine duplex structure of equiaxed L12 and B2 phases developed after complete recrystallization that showed significant resistance to grain growth up to very high annealing temperatures (∼1300 °C). The remarkable resistance to grain growth compared to conventional or even other single or dual phase HEAs was due to the formation of a homogeneous duplex structure where growth of one phase was effectively retarded by the other phase. The strong presence of the α-fiber components, but weak BR (236<385>) and D (113<332>) components in the recrystallization texture of the L12 /FCC phase was due to the absence of strong preferential nucleation or growth. Presence of ND-fiber (ND//<111>) with strong 111<011> component in the recrystallization texture of the B2 phase indicated ease of nucleation from similarly oriented regions in the deformed microstructure. Highlights: Deformation and annealing textures of eutectic (L12 +B2) HEA is reported. Brass type texture in L12 in cold-rolled EHEA. Remarkable resistance to microstructural coarsening during annealing. Strong α-fiber (ND//<110>) developed in the L12 /FCC after recrystallization. Strong ND (//<111>) fiber texture in the B2 phase in recrystallized EHEA.